Planificación tributaria de la empresa San Marcos de la ciudad de Babahoyo - Tapia Gómez, Mariela Belén (2021)
The Imprenta San Marcos, is located in the city of Babahoyo, since 1997 it is dedicated to providing printing services, and in 2014 it diversified its services activities of binding of printed sheets to make books, brochures, magazines, catalogs etc., by casting , cut, assembled, gummed, collated, basted (sewn), adhesive bound, trimmed, gold stamping, spiral binding, and so on. The central problem is that it does not keep an order and control of its tax returns, which has led to a bad economic investment of the San Marcos printing company. The main objective is to demonstrate the lack of adequate tax planning at the San Marcos printing company, which will allow me to demonstrate the existence of shortcomings that impede the normal development of activities. The scope of the case study is limited to knowing the impact of internal control applied to the tax obligations of the organization, through direct observation of financial information and previous tax returns. The study is framed under the research subline "Financial Management, Tax and Social Commitment" which is located and established in the research lines of the School of Accounting, Auditing and Finance